2022
DOI: 10.1038/s41598-022-15946-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and promise of a TCR mimic antibody for cancer immunotherapy of hepatocellular carcinoma

Abstract: Monoclonal antibodies are at the vanguard of the most promising cancer treatments. Whereas traditional therapeutic antibodies have been limited to extracellular antigens, T cell receptor mimic (TCRm) antibodies can target intracellular antigens presented by cell surface major histocompatibility complex (MHC) proteins. TCRm antibodies can therefore target a repertoire of otherwise undruggable cancer antigens. However, the consequences of off-target peptide/MHC recognition with engineered T cell therapies are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…CTA: cancer testis antigen, MHCA: MHC alpha chain, MHCB: MHC beta chain, Neo: neoantigen. *We have labelled the TCRm from 7RE7 as AFP-TCRm as it has no name in the seminal paper (28).…”
Section: Tional Link Between Antibody/tcr Chains Made By Analogous Ge...mentioning
confidence: 99%
See 3 more Smart Citations
“…CTA: cancer testis antigen, MHCA: MHC alpha chain, MHCB: MHC beta chain, Neo: neoantigen. *We have labelled the TCRm from 7RE7 as AFP-TCRm as it has no name in the seminal paper (28).…”
Section: Tional Link Between Antibody/tcr Chains Made By Analogous Ge...mentioning
confidence: 99%
“…Experimental peptidome binding assays performed on three early-generation TCRms (17,19,20) suggested that they were unlikely to achieve the levels of specificity required for therapeutic applications (21,22). However, several TCRms with apparently high specificity have been reported in the past year, fostering renewed interest in this therapeutic modality and resulting in a more than doubling of the num-ber of crystal structures of TCRm:pMHC complexes (23)(24)(25)(26)(27)(28). These include an anti-Wilms' Tumor Antigen 1 (WT1) TCRm ( 23) and an anti-alpha ferroprotein (AFP) TCRm (28) that have both progressed to clinical trials (23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental peptidome binding assays performed on three early-generation TCRms ( 17 , 19 , 20 ) suggested that they were unlikely to achieve the levels of specificity required for therapeutic applications ( 22 , 23 ). However, several TCRms with apparently high specificity have been reported in the past year, fostering renewed interest in this therapeutic modality and resulting in a more than doubling of the number of crystal structures of TCRm:pMHC complexes ( 24 29 ). These include an anti-Wilms’ Tumor Antigen 1 (WT1) TCRm ( 24 ) and an anti-alpha ferroprotein (AFP) TCRm ( 29 ) that have both progressed to clinical trials.…”
Section: Introductionmentioning
confidence: 99%